Agronomic Performance and Yield Potential of Promising Pigmented (Red and Black) Rice Lines In Medium-Altitude Paddy Fields - I Gusti Putu Muliarta Aryana; I Wayan Sudika; Ni Wayan Sri Suliartini; Fitriani Fitriani (Postgraduate, University of Mataram, 2026)
This study aimed to evaluate the agronomic traits and yield performance of several promising pigmented rice lines, including red and black rice, grown in medium-lowland paddy fields. The research was conducted from March to June 2025 at an altitude of 402 meters above sea level in Tampak Siring Village, Batukliang District, Central Lombok Regency. The experimental method used was a Randomized Complete Block Design (RCBD) consisting of 21 treatments, including 11 red rice lines, 4 black rice lines, and 4 parental lines (IPB3S, Situ Patenggang, Baas Selem, and the red rice promising line F2BC4P19-36), along with 2 check varieties, Impago Unram 1 and IR64. Each treatment was replicated three times, resulting in a total of 63 experimental units. The observed data were analyzed using analysis of variance (ANOVA), and significant differences among treatments were further tested using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the agronomic performance of both red and black rice lines exhibited medium maturity, with flowering time ranging from 83 to 93 days after sowing and harvesting time from 120 to 129 days after sowing. The number of productive tillers ranged from 12 to 19 tillers, panicle length ranged from 23 to 27 cm, the number of filled grains per panicle ranged from 130 to 147 grains, and grain weight per clump ranged from 33 to 41 grams. The highest grain yield was recorded in the red rice line G-2M (F7 IPB3S/F2BC4P19-63/FAT/F2BC44P19-63-PD3/15) at 4.99 t/ha, which was higher than its parental lines IPB3S (G1-6IPB3S) at 4.31 t/ha and GH Merah (G-20GHBM) at 3.83 t/ha. Among black rice lines, G-12H (F11BLK.SP/BS 2/1/1/P4) yielded 4.42 t/ha, compared to Baas Selem (G-18BS) at 3.86 t/ha, Situ Patenggang (G-17SP) at 4.63 t/ha, and the check variety IR64 (G-21IR64) at 3.60 t/ha.